2020
DOI: 10.1002/hon.2789
|View full text |Cite
|
Sign up to set email alerts
|

Targeted‐dose of busulfan: Higher risk of sinusoidal obstructive syndrome observed with systemic exposure dose above 5000 µMol⸱min. A historically controlled clinical trial

Abstract: Busulfan is given in the conditioning regimens preceding hematopoietic stem cell transplantation (HSCT), and plasma levels can be monitored. A targeted, individualized systemic exposure (SE) dose can be achieved by calculating the area under the plasma concentration versus time curve (AUC). The objective of this study was to determine a cutoff value for safety for the AUC for busulfan plasma levels in patients undergoing HSCT. A total of 149 consecutive HSCT patients were studied. After an oral test dose of bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
(66 reference statements)
1
3
0
Order By: Relevance
“…Esteves et al had shown that a higher dose of Bu would not reduce relapse rates, similar to our results [ 30 ]. Another study did show a difference on relapse rate and aGvHD linked to Bu-AUC, although acknowledging the possible role of HLA incompatibility in their results [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Esteves et al had shown that a higher dose of Bu would not reduce relapse rates, similar to our results [ 30 ]. Another study did show a difference on relapse rate and aGvHD linked to Bu-AUC, although acknowledging the possible role of HLA incompatibility in their results [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…With Bu-4, Andersson et al describe a target AUC of <1200 μmol/l to prevent significant hepatic toxicity, with a serious increase of SOS and neurological side effects with an AUC > 1500 μmol/l*min [ 23 ], even though the effect on SOS was not confirmed in another study [ 15 ]. With Bu-1, Esteves et al establish a target AUC < 5000 μmol/l*min [ 30 ]. An important multicenter retrospective study conducted in children defined a new optimal exposure AUC of 1225 to 1575 μmol/l*min with lower event-free survival as compared to children out of this range, particularly because of lower relapse probability at 2.5 years [ 31 ]; this higher target range is probably not applicable to adults because of toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The association between Busulfan exposure and outcomes in paediatric patients with varying malignant diagnoses, including ALL, has been reported in many studies (Table 1) (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). The therapeutic window for Busulfan recommended by the European Medicines Agency (EMA) is AUC 6h 900-1,500 µM.min (daily AUC of 14.8-24.6 mg.h/L) (56,57).…”
Section: Optimising the Use Of Busulfan-based Conditioning With Pharmacokinetics And Genomics Definition And Refinement Of The Optimal Bumentioning
confidence: 99%
“… 14 The variability in clinical outcomes is partly due to interpatient differences in busulfan pharmacokinetic (PK) and the narrow therapeutic window of systemic busulfan exposure. 15 Higher exposure has been reported to be associated with an increased risk of toxicity, such as mucositis, GVHD, veno-occlusive disease of the liver, and TRM, 13 , 16 , 17 whereas a low busulfan exposure has been associated with a higher probability of graft rejection, poor graft function, and disease relapse. 18 , 19 , 20 Therefore, the use of therapeutic drug monitoring (TDM) to target a specific area under the curve (AUC) in the more recent period after consensus 21 and/or concentration at steady state has historically provided a personalized approach to dosing to better ensure exposure within the narrow therapeutic window of efficacy and toxicity for each patient.…”
Section: Introductionmentioning
confidence: 99%